Evolution of water environment construction and urban landscape ecological risk based on land cover change analysis. (8th March 2022) - Gong, Xujie; Chen, Liangming; Tan, Shun
Abstract: Mining minerals plays a fundamental role in promoting social-economic progress. Intensive mining operations. However, it also brings huge ecological risks, and may lead to significant changes in land use/land cover (LULC), further affecting the urban landscape and ecological environment. Based on changes in LULC from 2000 to 2020 in the Jiawang district, a resource-based city, this study uses an ecological risk assessment as the theoretical basis for evaluating regional landscape ecological risk. The results show that: (1) From 2000 to 2020 significant changes in LULC were the increase the areas of built-up land and those covered with water, and decreases occurred in the cultivated, industrial, and mining land areas. The conversion of industrial and mining lands to areas of water is a noteworthy ecological compensation area. (2) Over the past two decades, the average ecological risk in the study area was 0.19, 0.21, and 0.14, in 2000, 2010 and 2020, respectively, first increasing and then decreasing. The area ratio of the lowest-risk ecological risk areas dropped from 31.60% to 4.00%. (3) The global Moran's I values in 2000, 2010, and 2020 were 0.6047, 0.6280, and 0.6392, respectively. The positive values indicate that the autocorrelation and spatial aggregation of ecological risks in Jiawang district gradually increased. This study can provide a basis for other resource-based cities to rationally allocate land resources and manage urban ecological risks.